(untitled) (Andamios, Revista de Investigación Social, 2011)
This article reviews some historical elements that Jose Tomás de Cuéllar novelized in El pecado del siglo (1869), historical novel that narrates a famous crime, which happened one century behind in times of the Revillagigedo viceroy (1789). It ponders about the Colonia’s reading done by the República Restaurada writers, and explores the writer’s workshop: the sources in which Cuéllar documented the matter, the transformation of the information in literature and the items without historical references that he interweaves in the story. All this elements are provided, for the reader to understand his own historical moment.